European cycling lexicon. - (:unkn) unknown (My University, 2009)
Das Fahrradlexikon übersetzt die Begriffe in 23 verschiedene Sprachen.
Keywords: Fahrradverkehr; Nachschlagewerk; Individualverkehr; Fahrradtechnik; Fahrradnutzung; Fahrradinfrastruktur; Fahrradtyp; Lexikon; Phrase